2016
DOI: 10.1007/s00380-016-0915-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgical left atrial appendage amputation/ligation on stroke prevention in patients undergoing off-pump coronary artery bypass grafting

Abstract: Stroke is a major adverse event in patients developing atrial fibrillation (AF) after cardiac surgery. Surgical left atrial appendage amputation/ligation (LAA-A/L) during off-pump coronary artery bypass grafting (OPCAB) is routinely performed in our institution. We analyzed 578 consecutive patients (mean age 69 years, male 82%) undergoing OPCAB with or without concomitant LAA-A/L from 2011 to 2014 at our institution in a prospective observational manner. The safety and efficacy of the concomitant LAA-A/L on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…This study showed that exclusion of LAA by closing it using a double‐layer suture during MVR reduced the incidence of ischemic stroke during hospitalization, particulary in patients with AF. It is consistent with several other observational studies 8‐15 where LAA exclusion has been recognized as a protective factor for different types of patients undergoing cardiac surgery (Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that exclusion of LAA by closing it using a double‐layer suture during MVR reduced the incidence of ischemic stroke during hospitalization, particulary in patients with AF. It is consistent with several other observational studies 8‐15 where LAA exclusion has been recognized as a protective factor for different types of patients undergoing cardiac surgery (Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, there are mixed data on the association between LAAO and risk of POAF. Of eight studies, five found no significant difference in the rate of POAF between the LAAO and no-LAAO groups [20,25,[28][29][30]. The other three studies found a significantly higher rate of POAF in the LAAO group compared to the no-LAAO group [10,26,27].…”
Section: Is Left Atrial Appendage Occlusion Associated With a Greater...mentioning
confidence: 92%
“…The studies conducted by Almahameed et al [23] and Yao et al [10] included a subgroup analysis of only patients that did not have preexisting atrial fibrillation. Notably, the studies by Johnson et al [24] and Endo et al [25] featured over 90% of patients without preexisting atrial fibrillation (Table 2).…”
Section: Key Pointsmentioning
confidence: 99%
“…In the LAA amputation group, the frequency of arrhythmia such as new AF after surgery (both groups: 30%) did not increase without the occurrence of adverse events, but detailed analysis of the changes such as that in BP following amputation and measurements of ANP and BNP are required. 52) …”
Section: Introductionmentioning
confidence: 99%